Evolution of the vaquita/totoaba socio‐ecological system in the Upper Gulf of California, Mexico - J. Alejandro Rodríguez‐Valencia; Luis Fueyo‐Mac Donald; Miguel Á. Cisneros‐Mata (Ecosphere)
Abstract The Upper Gulf of California (UGC) hosts a rich marine biodiversity. Complex climatic processes generate high biological productivity enabling the use of resources in a complex socio‐ecological processes (SEPs). Through a literature review, evolution and aggravation of the SEP over 50 years are analyzed. The crisis peaked in the last decade related to vaquita, an endangered marine porpoise at the blink of extinction, and the illegal catch of totoaba, an endangered fish species, both endemic. Over the first three decades, stakeholders defined positions, while disorder in fisheries and reduction of vaquita population occurred. Corrective actions were implemented during the last two decades including diversification of markets for local fisheries, development of fishing technologies, and environmental regulations. Most actions failed, consolidating an ill governance aggravated by poaching of totoaba and drug trafficking. The evolution of the conflict includes (1) transition from community passivity to conservation efforts, to resistance and collective violence against them; (2) transition in the design and implementation of conservation actions from civil organizations to the government, facilitated by the disengagement of philanthropic donors for conservation, and reduction of support for civil organizations; (3) interventions by the Mexican Navy coordinated with the Sea Shepherd Conservation Society; and (4) weakening of the International Committee for the Recovery of Vaquita an international scientific moral authority to propose vaquita conservation. The federal government and the local fishing sector currently discuss scenarios that aim to authorize use of driftnets and gillnets, contrasting with the predominant conservation logic.